(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2016)
The experiment was conducted with twenty one genotypes of potato at the experimental farm of Sher-e-Bangla Agricultural University, Dhaka during the period from November 2014 to March 2015 to estimate the genetic variability and diversity among the genotypes. The experiment was conducted using Randomized Complete Block Design with three replications. All the genotypes varied significantly with each other for all the studied characters indicated the presence of considerable variations among the genotypes studied As per PCA, D2 and clusters analysis the genotypes were grouped into five different clusters. Clusters III had the maximum nine and cluster II and V had the minimum one genotype. The highest inter-cluster distance was observed between I and V and the lowest was observed between IV and V. Genotypes in cluster I showed the maximum performance for number of leaves per plant, chlorophyll percentage, weight of individual potato and firmness. Cluster II showed maximum performance for total soluble sugar. Cluster III recorded the highest mean performance for dry matter. Cluster IV showed the maximum performance for number of potato per hill, weight of potato per hill and yield. Cluster V showed the maximum performance for specific gravity. Considering this idea and other characteristic performances, G8 (Shada pakri) and G17 (Shil bilati) from cluster IV; G4 (BARI-TPS-1) from cluster II; and G6 (Asterix), G21 (Granola) , G1 (Cardinal) and G2 (Diamant) from cluster I might be considered better parents for efficient hybridization programme.